EU–India Cooperation on Climate Change: Opportunities and Challenges in Achieving Global Sustainability (Journal of Advances and Scholarly Researches in Allied Education, 2025)
It will be possible to achieve sustainable development when the whole world will take the joint action in response to the climate change, which is one of the most serious problems of the century. India and European Union (EU) are the key actors with vast impacts throughout the world economy, people, and ecosystems. Learning about the scope, opportunities, and challenges of these types of collaborations, this thesis explores the issue of climate change partnership between the European Union and India in the context of sustainability on the global scale. The paper explores how these two are converging in relation to the development of clean energy linkages, the Paris Agreement, and climate policy though each has different priorities in its development. To determine the extent of bilateral cooperation, this qualitative and analytical research uses secondary data gathered using government papers, policy documents and international organisations. The results of this study indicate that there are many opportunities that the European Union and India can collaborate in such as renewable energy production, transfer of green technology, sustainable infrastructure, and international climate regulation. However, there are still certain challenges, including as disparities in economics and regulation, lack of resources, and competing national interests. All of these variables can make the process of coordinating and implementing the policies more difficult. It puts forward the idea that, although all has been getting better with time, a more inclusive, flexible, and egalitarian system is required to establish efficacy. The paper discusses that to create an impact on sustainability at a global level, as well as bilateral benefits, climate cooperation and collaboration between the European Union and India is essential. By collaborating in a more systematic manner, North-South collaboration will help address climate change and build a more resilient economy with a smaller carbon impact.